Mannose-Binding Lectin Gene Polymorphisms in Infants with Bronchiolitis and Post-Bronchiolitis Wheezing - Kirsi Nuolivirta; Qiushui He; Kirsi Gröndahl-Yli-Hannuksela; Petri Koponen; Matti Korppi; Merja Helminen (Allergology International, 2012)
Background: Mannose-binding lectin (MBL) encoded by the MBL2 gene, is an important component of the innate immunity. Low levels have been linked with respiratory infections and both high and low levels with allergy and asthma. The aims of the study were to evaluate the connection between polymorphisms of the MBL2 gene and viral findings, clinical characteristics and subsequent wheezing in young infants with bronchiolitis. Methods: In all, 129 full-term infants hospitalized for bronchiolitis at age less than 6 months have been followed-up until the mean age of 1.5 years. The genotyping of the MBL2 gene mutations was made by pyrosequencing for a simultaneous detection of three single nucleotide polymorphisms (SNP). Results: The MBL genotypes or allele frequencies had no significant associations with clinical characteristics of bronchiolitis. The 41 children with variant genotypes were more often infected by multiple viruses (21.9%, p = 0.047) than children with wild-type A/A genotypes (9.1%). In addition, more children with variant genotypes (31.7%, p = 0.016) had used corticosteroids because of post-bronchiolitis wheezing, compared to those with wild-type A/A genotypes (13.6%). No other significant associations with viral findings or post-bronchiolitis outcomes were found. Conclusions: Preliminary evidence was found that the variant non-A/A genotypes may be associated with susceptibility to multiple viral infections and more severe post-bronchiolitis wheezing requiring treatment with corticosteroids.